2010
DOI: 10.1094/pdis-94-8-1062c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Spot Form of Net Blotch of Barley Caused by Pyrenophora teres f. maculata in Hungary

Abstract: A countrywide survey of fungal diseases of barley (Hordeum vulgare L.) was conducted from 2005 to 2009. Unusual leaf necrosis varying in shape from 1 × 2 mm necrotic flecks to 15 × 20 mm ovoid spots was found. Sometimes a chlorotic halo surrounding the dead area was observed. Lesions appeared on various cultivars in many commercial fields and experimental plots at a number of sampling sites. Symptomatic leaves were taken to the laboratory and incubated in a moist chamber at room temperature on the bench to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Ptt was present in all of the sampled areas in France, whereas Ptm was only found in the southwest of the country, where it coexisted with Ptt in the same field. This pattern is similar to what has been reported in other regions of Eastern and Northern Europe, North America, Italy, the Maghreb, and Egypt, where the two forms are present, but Ptt clearly predominates [37, 46, 59, 6272]. Our results, however, contrast with what was observed in East Africa, South Africa, and Southeastern Australia, where Ptm is more prevalent [44, 61, 73].…”
Section: Resultssupporting
confidence: 90%
“…Ptt was present in all of the sampled areas in France, whereas Ptm was only found in the southwest of the country, where it coexisted with Ptt in the same field. This pattern is similar to what has been reported in other regions of Eastern and Northern Europe, North America, Italy, the Maghreb, and Egypt, where the two forms are present, but Ptt clearly predominates [37, 46, 59, 6272]. Our results, however, contrast with what was observed in East Africa, South Africa, and Southeastern Australia, where Ptm is more prevalent [44, 61, 73].…”
Section: Resultssupporting
confidence: 90%
“…Ptt was present in all of the sampled areas in France, whereas Ptm was only found in the southwest of the country, where it coexisted with Ptt in the same field. This pattern is similar to what has been reported in other regions of Eastern and Northern Europe, North America, Italy, the Maghreb, and Egypt, where the two forms are present, but Ptt clearly predominates [37, 46, 64, 80, 83–92]. Our results, however, contrast with what was observed in East Africa, South Africa, and Southeastern Australia, where Ptm is more prevalent [44, 82, 93].…”
Section: Resultssupporting
confidence: 89%
“…Sexual outcrossing may generate new pathogen genotypes with increased genetic diversity and rapid adaptability to host genotypes with different levels of disease resistance [79]. It was demonstrated that the Hungarian Ptt population is genetically diverse, and both mating types are common in both commercial and experimental fields [51,52]. Perhaps sexual reproduction and the diverse collections of breeding lines/cultivars with variable resistance against Ptt have contributed to a diverse pathogen micro-population at the sampling sites.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus has also been identified in wheat in Hungary [ 50 ]. A survey from 2006 to 2010 confirmed the abundance and high genotypic diversity of Ptt in both commercial and experimental fields of barley and wheat throughout Hungary [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%